2020
DOI: 10.4082/kjfm.18.0130
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Health Status in Primary Care Underserved Area Residents and the General Population in Korea

Abstract: Background: This study compared chronic diseases and health-related quality of life (HRQoL) in between primary care underserved areas residents and the general population. Methods: Underserved areas were identified according to accessibility and the time relevance index for primary care. Overall, 279 participants aged ≥60 years from four counties enrolled voluntarily. A total of 1,873 individuals were assigned in the control group using the Korea National Health and Nutrition Examination Survey database. We as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 18 publications
0
5
0
5
Order By: Relevance
“…Kim et al used TRI to identify medically underserved areas and found that hypertension in residents of such areas was undiagnosed and under-controlled. 19 Specifically, the actual prevalence did not differ significantly between the two groups, whereas awareness (OR, 0.40; 95% CI, 0.25–0.64, P < 0.001) and disease control (OR, 0.27; 95% CI, 0.18–0.41, P < 0.001) were lower in the underserved areas than that in the general population. 19 Another study of patients, aged over 70 years, with chronic diseases also used TRI to evaluate access to medical services.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Kim et al used TRI to identify medically underserved areas and found that hypertension in residents of such areas was undiagnosed and under-controlled. 19 Specifically, the actual prevalence did not differ significantly between the two groups, whereas awareness (OR, 0.40; 95% CI, 0.25–0.64, P < 0.001) and disease control (OR, 0.27; 95% CI, 0.18–0.41, P < 0.001) were lower in the underserved areas than that in the general population. 19 Another study of patients, aged over 70 years, with chronic diseases also used TRI to evaluate access to medical services.…”
Section: Discussionmentioning
confidence: 79%
“… 19 Specifically, the actual prevalence did not differ significantly between the two groups, whereas awareness (OR, 0.40; 95% CI, 0.25–0.64, P < 0.001) and disease control (OR, 0.27; 95% CI, 0.18–0.41, P < 0.001) were lower in the underserved areas than that in the general population. 19 Another study of patients, aged over 70 years, with chronic diseases also used TRI to evaluate access to medical services. 37 They studied the relationship between medical experience, including medical accessibility, and unmet medical health care perception in areas with a TRI of less than 30%.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This result is higher than the estimated EQ-5D utility scores of 0.64 for those diagnosed with PAD within one year [23,28], 0.73 for symptomatic patients with PAD [29], and 0.79 for chronic obstructive pulmonary disease in patients living with PAD [30]. However, this is lower than the estimated EQ-5D utility scores of 0.87 for the general population over 60 years in Korea [31]. This result suggests that PAD is a risk factor in lowering HRQOL and that HRQOL could be further reduced depending on comorbid diseases or symptoms.…”
Section: Discussionmentioning
confidence: 72%
“… 50 51 In Korea, medical facilities are predominantly concentrated in metropolitan areas and large cities 52 and the concentration of population in large cities further exacerbates the concentration of healthcare resources in these areas, resulting in disparities in medical utilization. Because insufficient primary care can contribute to poor control of chronic diseases and quality of life, 53 we suggest that a national approach to ensure an even distribution of medical institutions capable of providing primary care and early screening is needed. Considering these possibilities, future studies could explore the relationship between regional characteristics and YLLs and YLDs measurements from this study to identify geographical health risks.…”
Section: Discussionmentioning
confidence: 99%